APLIKASI SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMAN 6 TANGERANG SELATAN - Dinda Alfhia Syahrina, (2021)
Academic Information System (SIAKAD) is a system that functions to facilitate schools in the process of managing academic data and delivering academic information. SMA Negeri 6 Tangerang Selatan in managing academic data and delivering academic information is still not effective. So far, the delivery of academic information carried out by SMAN 6 South Tangerang is still in oral, written, or via telephone or electronic messages. This can lead to a slow process of delivering and receiving academic information at SMA Negeri 6 Tangerang Selatan. For this reason, researchers will build SIAKAD which can provide accurate and up-to-date academic information and make it easier for schools to manage academic data. In making this system, researchers used the PIECES analysis method to analyze system requirements and the waterfall method as a software design method. This research produces a web-based academic information system that will be useful in accordance with the needs of the school at SMAN 6 Tangerang Selatan Keywords: Academic Information Systems, PIECES, Waterfall, SMAN 6 Tangerang Selatan